Graduate and employment: a case study on the diploma in banking programme at MARA University of Technology, Sarawak Branch/ Annie Wong Muk Ngiik and Voon Boo Ho - Wong, Annie Muk Ngiik; Voon, Boo Ho (2002)
The graduates' progress after they have completed their studies needs to be addressed. This is useful for future planning and improvement. Empirical evidences on graduate employment are obtained through a tracer study on Diploma in Banking graduates. This study focuses on the graduates who have completed their studies from UiTM Sarawak Campus from the year 1993 to the year 2000. The main aim of this study is to evaluate the employability of the graduates and the relevance of the course in relation to their current employment. A total of 240 (39.2% response rate) usable mail questionnaires are collected and analyzed. The main variables studied include, graduates' academic achievement, their employment pattern, further educational opportunities, as well as suggestion for improvement for the programme. The findings. indicate that quite a significant proportion of graduates (42%) go for further study after their graduation. The employment rate among the respondents is quite high (75%) and most of them waited for a relatively short period (about 12 months) to secure their first employment. On the average they earn between RM 500 to RM 2000 per month. As a whole, they perceived most of the core and non core subjects as important and relevant to their present work. The exceptions are subjects like other languages and religious studies.